The Role of Digital Literacy in Reducing Students’ English-Speaking Anxiety among Indonesia EFL Learners: A Systematic Literature Review - Ervin Okta Viani; Mai Zuniati; Umar Al faruq A.Hasyim (Universitas Islam Negeri Palopo, 2026)
English speaking anxiety remains a major affective barrier among Indonesian EFL learners, compounded by sociocultural norms of face-saving and limited authentic speaking practice in traditional classroom settings. Despite growing interest in technology-enhanced language learning, prior research has largely examined digital tools in isolation rather than as an integrated competency framework, leaving a gap in understanding how digital literacy functions holistically as an affective support system. This study examined the role of digital literacy in reducing English speaking anxiety, identified the most effective digital literacy components, and synthesized key findings from prior research. A Systematic Literature Review (SLR) following the PRISMA 2020 protocol was conducted across Google Scholar and ERIC databases. From 1,490 initially retrieved records, 20 empirical articles published between 2020 and 2025 were systematically selected and analyzed. A key novelty of this study lies in its application of Indonesia’s National Digital Literacy Framework (Kominfo) as the sole analytical lens—a methodological choice grounded in national educational policy rather than generic Western-derived models. This framework conceptualizes digital literacy through four pillars: Digital Skills, Digital Ethics, Digital Safety, and Digital Culture. Findings demonstrate that digital literacy reduces speaking anxiety through three interrelated mechanisms: alleviating performance pressure via asynchronous platforms; creating psychologically safe practice environments through AI-based tools; and fostering confidence through repetitive digital practice. These findings confirm that digital literacy functions not merely as a technical competency but as a holistic affective support system for EFL learners. For EFL educators, these findings suggest that instructional designs integrating asynchronous speaking tasks, AI-based feedback tools, and culturally sensitive digital scaffolding can meaningfully lower the affective filter and promote communicative confidence among Indonesian learners.